YUKAWA COUPLINGS FOR A 3-GENERATION SUPERSTRING COMPACTIFICATION - Candelas, P; Kalara, S (1988)
We explicitly calculate the Yukawa couplings for a three-generation superstring compactification and show in detail how the calculation reduces to algebraic manipulations of certain polynomials. We also discuss the form of the low energy effective theory and find a basis for which these terms are diagonal. © 1988.